Bundling objects, documents, and practices: Collecting Andean mummies from 1850 to 1930. Issue 1 (2nd January 2019) - Ordoñez, Maria Patricia
ABSTRACT: This article presents research on the relationship between objects, documents, and the practice of collecting Andean mummies by European national museums in the period from 1850 to 1930. Over 200 mummies were analysed as part of this research. These mummies are kept by 18 different national museums in Western European countries. The comparative examination of these mummified human remains and their associated documentation kept by the museums has highlighted the importance of considering the process of formation of collections. This is especially true when dealing with sensitive archaeological 'objects' during a specific historical timeframe, and within a contemporary setting. The importance of considering museum collections as embedded in global narratives, rather than isolated cases of collecting, is also highlighted in this article.